1999
DOI: 10.1063/1.371583
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magneto-optic properties of orthoferrite thin films grown by pulsed-laser deposition

Abstract: Thin magnetic layers have been prepared by pulsed-laser deposition from targets of the orthoferrites: DyFeO3, GdFeO3, SmFeO3, and YFeO3. All layers were deposited onto quartz substrates at a temperature of 450 °C under high-vacuum conditions, i.e., in the absence of additional oxygen. The as-grown films show evidence of the following phases: RFeO3, R3Fe5O12, Fe3O4, and R2O3, where R=Dy, Gd, Sm, and Y. The magnetic properties of these films have been investigated using superconducting quantum interference devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 15 publications
2
30
1
1
Order By: Relevance
“…1 shows powder X-ray diffraction pattern for the Dy 0.75 Fe 1.25 O 3 orthoferrite samples calcined at 600 1C (a) and 700 1C (b), respectively. We can easily see that the positions of the XRD peaks coincide exactly with the standard ones reported in the literature [13,17]. When the brittle flakes were calcined at 600 1C, the samples show a poor crystallization, only the main peak is observed.…”
Section: Article In Presssupporting
confidence: 84%
See 2 more Smart Citations
“…1 shows powder X-ray diffraction pattern for the Dy 0.75 Fe 1.25 O 3 orthoferrite samples calcined at 600 1C (a) and 700 1C (b), respectively. We can easily see that the positions of the XRD peaks coincide exactly with the standard ones reported in the literature [13,17]. When the brittle flakes were calcined at 600 1C, the samples show a poor crystallization, only the main peak is observed.…”
Section: Article In Presssupporting
confidence: 84%
“…For the samples calcined at 700 1C, the magnetization always increases smoothly with magnetic field increasing, indicating the hard magnetic feature of Dy 0.75 Fe 1.25 O 3 nanoparticles. Let us look at the difference between the ascending (points going from negative magnetic field to positive magnetic field) and descending (points going from positive magnetic field to negative magnetic field) portions of the hysteresis loop by subtracting their values of magnetic moment for the various value of magnetic field [13,22]. The obtained results (named as difference curve) for the samples calcined at 600 1C (a) and 700 1C (b) are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the fabrication of rare-earth iron garnet R 3 Fe 5 O 12 [12], orthoferrite RFeO 3 films [13], and hexagonal M-type barium ferrite BaFe 12 O 19 [14], the as-deposited films should be annealed at least above 800 1C for the growth of single-crystalline films. These facts indicate that solid state epitaxy at high temperature is more dominant in the crystal growth of complex oxides than the gas phase reaction during film deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Flux melts, liquid phase epitaxy LPE [1] and the sputtering techniques have been used in the past to prepare thin film of ferrites [2] . It was shown that the film of spinel ferrite can be formed by using the pulsed laser deposition technique [3,4,5] . The experimental result, illustrates the change of XRD patterns upon annealing at high temperatures.…”
Section: Introductionmentioning
confidence: 99%